Babamunida debrae, a new species of squat lobster (Crustacea: Anomura: Galatheoidea: Munididae) from the Hawaiian Islands - Baba, Keiji (Zootaxa, 2011)
A new species of squat lobster, Babamunida debrae, was found in shallow waters of the west coast of Hawai‘i. It is readily distinguished from all the other species of the genus by the presence of a pair of spines on the second abdominal tergite. Babamunida debrae is the second species of the genus from Hawaii and seventh species of the genus from the Indo-Pacific.